(untitled) (Communications in Computational Physics, 2018)
We use a generalized scaling invariance of the dispersion-managed nonlinear Schrödinger equation to derive an approximate function for strongly dispersion-managed solitons. We then analyze the regime in which the approximation is valid. Finally, we present a method for extracting the underlying soliton part from a noisy pulse, using the resulting approximate formula.